2018
DOI: 10.26737/jpipsi.v3i2.712
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Media Video Terhadap Kesiapsiagaan Siswa Dalam Menghadapi Bencana Gempabumi Di Sma Negeri 1 Gantiwarno, Klaten

Abstract: <p><strong><em>.  </em></strong>Penelitian ini  bertujuan  mengetahui  penggunaan  media  video  terhadap  kesiapsiagaan siswa  menghadapi bencana gempabumi di SMA Negeri 1 Gantiwarno. Penelitian ini dilakukan dengan pendekatan deskriptif kuantitatif sebelumnya dilakukan uji prasyarat analisis menggunakan metode <em>Kolmogorov Smirnov </em>untuk uji normalitas dan metode <em>Levene Test </em>untuk uji homogenitas, dengan populasi siswa SMA Negeri 1 Gantiwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
2
5
0
1
Order By: Relevance
“…This study is in line with Wulandari (2018) research it reported that educational videos positively impact students in increasing preparedness to face earthquakes. In addition, a theory explains that good knowledge in preparedness will form good practice or attitude (Supriyono, 2014).…”
Section: Earthquake Disaster Preparedness After Being Provided With Educational Videosupporting
confidence: 92%
“…This study is in line with Wulandari (2018) research it reported that educational videos positively impact students in increasing preparedness to face earthquakes. In addition, a theory explains that good knowledge in preparedness will form good practice or attitude (Supriyono, 2014).…”
Section: Earthquake Disaster Preparedness After Being Provided With Educational Videosupporting
confidence: 92%
“…This study produces learning media that has an attractive appearance and takes advantage of technological advances so as to make it easier for students to learn contextual learning (Mutlu & Kayabaş, 2015). In line with the results of the research which states that the provision of video and audio-visual media makes the level of readiness of students in the ready category and increases students' knowledge to be tough, agile, and responsive to earthquake disasters (Sari & Suciana, 2019;Wulandari, 2018).…”
Section: Resultssupporting
confidence: 63%
“…Preparedness is an appropriate and effective action during a disaster or post-disaster that is important for individuals to be able to maintain themselves and anticipate disasters (Wulandari 2018). Research on the development of learning media for e-magazine disease outbreak disaster mitigation using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation).…”
Section: Resultsmentioning
confidence: 99%